Deletions and de novo mutations of SOX11 are associated with a neurodevelopmental disorder with features of Coffin–Siris syndrome. Issue 3 (5th November 2015) - Hempel, Annmarie; Pagnamenta, Alistair T; Blyth, Moira; Mansour, Sahar; McConnell, Vivienne; Kou, Ikuyo; Ikegawa, Shiro; Tsurusaki, Yoshinori; Matsumoto, Naomichi; Lo-Castro, Adriana; Plessis, Ghislaine; Albrecht, Beate; et al.
Abstract : Background: SOX11 is a transcription factor proposed to play a role in brain development. The relevance of SOX11 to human developmental disorders was suggested by a recent report of SOX11 mutations in two patients with Coffin–Siris syndrome. Here we further investigate the role of SOX11 variants in neurodevelopmental disorders. Methods: We used array based comparative genomic hybridisation and trio exome sequencing to identify children with intellectual disability who have deletions or de novo point mutations disrupting SOX11 . The pathogenicity of the SOX11 mutations was assessed using an in vitro gene expression reporter system. Loss-of-function experiments were performed in xenopus by knockdown of Sox11 expression. Results: We identified seven individuals with chromosome 2p25 deletions involving SOX11. Trio exome sequencing identified three de novo SOX11 variants, two missense (p.K50N; p.P120H) and one nonsense (p.C29*). The biological consequences of the missense mutations were assessed using an in vitro gene expression system. These individuals had microcephaly, developmental delay and shared dysmorphic features compatible with mild Coffin–Siris syndrome. To further investigate the function of SOX11, we knocked down the orthologous gene in xenopus. Morphants had significant reduction in head size compared with controls. This suggests that SOX11 loss of function can be associated with microcephaly. Conclusions: We thus propose that SOX11 deletion or mutation can present with a Coffin–Siris phenotype.